Cambodia-U.S. Paradoxical Relations in Post-Cold War Era: The China Factor - Channtha So; Vannak Ro; Md Nadim Aktar (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This article investigates the structural paradox characterizing Cambodia-U.S. relations in the post-Cold War period, in which the persistence of political and security friction coexists with functional cooperation. The study identifies policy areas in which China’s emergence as an unconditional patron creates tension with the U.S., and analyzes mechanisms through which Chinese support enables Cambodia to evade U.S. normative pressure on democracy and human rights. Using an analytic eclecticism approach that combines structural realism and liberal institutionalism, the study conducts a qualitative content analysis of semi-structured interviews with 13 elite informants, including Cambodian government officials, U.S. diplomats, and analysts. The findings demonstrate that China’s multidimensional assistance (economic, military, and diplomatic) has significantly undermined Western normative leverage, forcing Cambodia to pursue a dual-track strategy that focuses conflict in the high-politics domain (security, governance) and maintains cooperation in the low-politics domain (trade, development assistance, public health). This pattern generates a state of managed contradiction, which compartmentalizes the coexistence of political hostility and functional cooperation without progressing towards normative convergence or bilateral breakdown. The study makes an empirical contribution by tracing how patron diversification reshapes small-state agencies and by showing that alternative patronage enables states to resist normative pressure while preserving selective cooperation in an era of great-power competition.